2019
DOI: 10.1155/2019/1431726
|View full text |Cite
|
Sign up to set email alerts
|

Jiedu Sangen Decoction Inhibits the Invasion and Metastasis of Colorectal Cancer Cells by Regulating EMT through the Hippo Signaling Pathway

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors affecting the digestive tract. Moreover, the invasion and metastasis of CRC are the main reason therapy is usually inefficient. Decreased intercellular adhesion and enhanced cell motility induced by epithelial-mesenchymal transition (EMT) provide the basic conditions for the invasion and metastasis of the epithelial tumor cells of CRC. The Jiedu Sangen Decoction (JSD) is a prescription that has been used for more than 50 years in the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Related proteins were detected to explore the mechanism of the EVA1A on EMT and apoptosis progression. Recent studies have provided enormous evidences suggesting that the Hippo signalling pathway can induce EMT 17,27,28 . Results revealed that compared with the control group, the Si‐ EVA1A group showed decreased N‐cadherin, vimentin and Bcl‐xL expression and increased Bax expression (Figure 6B).…”
Section: Resultsmentioning
confidence: 96%
“…Related proteins were detected to explore the mechanism of the EVA1A on EMT and apoptosis progression. Recent studies have provided enormous evidences suggesting that the Hippo signalling pathway can induce EMT 17,27,28 . Results revealed that compared with the control group, the Si‐ EVA1A group showed decreased N‐cadherin, vimentin and Bcl‐xL expression and increased Bax expression (Figure 6B).…”
Section: Resultsmentioning
confidence: 96%
“…6,7 For example, Jiedu Sangen Decoction, which has been used in the treatment of colorectal cancer (CRC) for over 50 years, has the ability to suppress the migration and invasion of CRC cells. 8,9 In addition, TCM has been long applied for the treatment of HCC. Besides, transcatheter arterial chemoembolization combined with JDF was shown to improve the prognosis of patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Wing lam et al reported that PHY906 reduced the CPT-11-induced gastrointestinal toxicity by inhibiting multiple steps of inflammation and the promotion of intestinal progenitor cell repopulation (20). Extensive studies have revealed that TCM antitumor drugs work by inhibiting tumor proliferation, promoting tumor apoptosis, and affecting diverse molecular targets (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%